Peritoneal Cells Mediate Immune Responses and Cross-Protection Against Influenza A Virus - Gautam, Avishekh; Park, Byoung Kwon; Kim, Te Ha; Akauliya, Madhav; Kim, Dongbum; Maharjan, Sony; Park, Joongwon; Kim, Jinsoo; Lee, Hanseul; Park, Man-Seong; Lee, Younghee; Kwon, Hyung-Joo (Frontiers in Immunology, 2019)
Intraperitoneal inoculation with live influenza A virus confers protection against intranasal infections in mice and ferrets. However, the responses of peritoneal cells to influenza A virus have not been investigated. Here we show that intraperitoneal inoculation with A/WSN/1933 (H1N1) virus induced virus-reactive IgG production in the peritoneal cavity in mice. The infection resulted in substantial but transient B cell and macrophage depletion along with massive neutrophil infiltration, but virus growth was not detected. Influenza A viruses bound to α-2,6-linked sialic acids of B cells and macrophages and induced apoptotic death of peritoneal cavity cells. However, re-infection with A/WSN/1933 virus did not have adverse effects on immune cells most likely because of the neutralizing antibodies produced in response to the first exposure. Infection of BALB/c mice with A/WSN/1933 induced cross-protection against an otherwise lethal intraperitoneal dose of A/Hongkong/4801/2014 (H3N2) virus. This information suggests that immunological responses in the peritoneal cavity can induce effective defense against future virus infection. Considering the unexpected potent immunoregulatory activity of the peritoneal cells against influenza viruses, we suggest that comparative studies on various immune reactions after infection through different routes may contribute to better selection of vaccination routes in development of efficacious influenza vaccines.